Online Spatial Cancer Registry System for Nigeria - Idowu, Peter Adebayo; Williams, Kehinde Oladipo; Alonge, Bunmi; Sarumi, Olusegun Ajibola (British Journal of Healthcare and Medical Research, 2015)
Cancer has become a major source of morbidity and mortality globally. The incidence of cancer is rising as well as in Nigeria as it continues to eat deep into the nation claiming lives of both prominent and less prominent citizens of the country. This disease is increasingly taking the lives of productive citizens thereby adding to the poverty level of the nation. In this paper, we present a system which was developed for population based cancer registry in Nigeria. This system is an online system with spatial features. The online spatial cancer registry for Nigeria was developed using Adobe Dreamweaver and Notepad++ as the Integrated Development Environments, HTML, CSS and JavaScript were used for the frontend, PHP was used as the scripting language, and MySQL with google map. The software used were open source which ensured that the application would be robust, reusable, cheap and highly scalable. The result of the developed system shows that health officers, policy makers and all other authorized stakeholders would be able to register, login, and run queries on information that has been previously entered into the system. With the system, the spatial distribution of cancer in any location in Nigeria can be easily visualized and query. Policy makers and authorized users would be able to visualize and query the system in order to take appropriate steps in addressing cancer in Nigeria. In conclusion, this system will help create national database for cancer patients and be able to analyse the spatial distribution of cancer and the system is user-friendly.